Social support and psychological distress of patients with pituitary adenomas: chain-mediated effects of self-efficacy and rumination - Lating Zhang; Lating Zhang; Na Cheng; Shan Zhang; Xinhui Liang; Yao Jia; Xue Jiang (Frontiers in Psychology)
IntroductionPsychological distress in patients with pituitary adenomas affects their quality of life and is influenced by various aspects such as sociocultural factors, personal resources, and stressors. Therefore, the aim of this study was to investigate the chain-mediated role of self-efficacy and rumination in the relationship between social support and psychological distress.MethodsThe study was based on the Wilson-Cleary model of health-related quality of life and self-efficacy theory. We investigated 500 patients with surgically treated pituitary adenomas in three tertiary hospitals in Shaanxi Province, China. We used the “Social Support” and “General Self-Efficacy” scales, “Rumination Scale,” and the “Psychological Distress in Patients with Pituitary Adenomas” questionnaire to conduct the survey, and the data were analyzed using structural equation modeling and bootstrap methods to examine the relationships between the variables.ResultsThe results showed that there was a significant positive correlation between social support and self-efficacy, social support and self-efficacy negatively predicted rumination and psychological distress, respectively. Rumination significant positive correlation with psychological distress, and social support, indirectly affected psychological distress through the chain-mediated effect of self-efficacy and rumination. This represents a compound multiple mediating effect on psychological distress.DiscussionClinical practitioners should enhance social support for patients with pituitary adenomas, improve patients’ self-efficacy, and mitigate rumination to reduce patients’ psychological distress.